The arrangement of the ansa spiralis of the Corriedale sheep colon (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1971)
An analysis of the arrangement of the ansa spiralis of 100 Corriedale sheep colons showed that 93 (93,0% ± 2,55) had regular patterns: 56 (60,21% ± 5,07) were seen with three centripetal and three and a half centrifugal coils, 30 (32,26% ± 4,85) with three and a half centripetal and four centrifugal coils, 6 (6,45% ± 2,54)with two and a half centripetal and three centrifugal coils and 1(1,08% ± 1,07) with four centripetal and four and a half centrifugal coils; the remaining 7 colons (7,0% ± 2,55) were observed with irregular spirals.